PARENT SATISFACTION WITH TREATMENT AND CARE SERVICES WITHTIN THE FRAMEWORK OF PEDIATRIC PALLIATIVE CARE IN LATVIA - Kalnina, Inta; Deklava, Liana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The number of children prenatally or after birth diagnosed with a disease with no prevent radical treatment options in Latvia and worldwide constantly increases. Pediatric palliative care in Latvia is organized in the form of a home hospice care model. It is instrumental to establish the level of patients’ satisfaction with the provided care and treatment services. The objective of the study is to evaluate patient satisfaction with care and treatment services under the offered pediatric palliative care model. The study sample comprises 153 parents with children receiving palliative care services. The study is based on the quantitative research method: patient satisfaction survey. The parental satisfaction was measured in six subcategories: networking and collaboration, follow-up care, funding, access, clinical capacity building and outreach. According to the outcomes of the study, the level of satisfaction with the provided treatment and care services under the hospice palliative care model is average. The lowest score was given to collaboration and access categories, whereas the highest score was awarded for the continuity (follow-up) of care and funding.